Broad scale functional connectivity for Asian elephants in the Nepal-India transboundary region. (1st November 2022) - Neupane, Dinesh; Baral, Suraj; Risch, Thomas S.; Campos-Arceiz, Ahimsa
Abstract: The Nepal-India transboundary region hosts one of Asia's most complex large mammal assemblages, including a small (but growing) population of Asian elephants ( Elephas maximus ). These elephants occur in four widespread and geographically disjunct subpopulations, and some of them undergo seasonal transboundary movements. We conducted a broad-scale evaluation of the amount and quality of elephant habitat available in the region and of functional landscape connectivity between and within subpopulations using Maxent, circuit theory, and least-cost path analysis. Habitat suitability was highly influenced by abiotic geographical factors (altitude and precipitation) and less by ecological factors (habitat heterogeneity, plant productivity) and human disturbance (distance to settlements). The region had a relatively small amount of high and optimal suitability habitat (12.6% out of 93, 700 km 2 ) but all subpopulations seem to be far from carrying capacity, suggesting ample potential for further population growth. Landscape connectivity was higher between and within the west and far-west subpopulations, which should be considered a single subpopulation. The central and ea st subpopulations, however, had low to very low between-subpopulation connectivity. Conservation priorities include maintaining the current connectivity in the west subpopulation and across the border in the east, and protecting high-quality habitats in eastern Nepal. Restoring connectivity between the central and other subpopulations is possible if the number of elephants continues growing, and it should be a long-term conservation aspiration. Maintaining and enhancing landscape connectivity in this region requires transboundary cooperation and coordination between Nepali and Indian authorities. If successful, it will bring considerable benefits for the conservation of elephants and other wildlife. Highlights: The Nepal-India transboundary region hosts a small, growing, fragmented, and widespread population of Asian elephants. We evaluated habitat suitability (Maxent) and landscape connectivity (circuit theory and least-cost path) between and within subpopulations. We found relatively low habitat suitability and identified the most important patches for connectivity The central subpopulation was relatively isolated, while transboundary connectivity was high at the extremes of the study area There is potential to restore connectivity, connecting all the subpopulation with much larger elephant populations in India.